The labor and health economics of breast cancer - Alexander Ahammer; Gerald J. Pruckner; Flora Stiftinger (Johannes Kepler University of Linz, Department of Economics, 2024)
We estimate the long-run labor market and health effects of breast cancer among Austrian women. Compared to a random sample of same-aged non-affected women, those diagnosed with breast cancer face a 22.8 percent increase in health expenses, 6.2 percent lower employment, and a wage penalty of 15 percent five years after diagnosis. Although affected women sort into higher quality jobs post-diagnosis, this is offset by a reduction in working hours. We argue that the hours reduction is more likely driven by an increase in the time preference rate, meaning that patients increasingly value the present over the future, rather than by an incapacitation effect or employer discrimination.
Keywords: I10; J22; I12; 330; Breast cancer; labor supply; health shocks; time discounting